Dispersion of graphene-based nanocarbon fillers in polyamide 66 by dry processing and its effect on mechanical properties. (1st April 2017) - Kim, Jongwon; Oh, Jinwoo; Lee, Kyung Yeol; Jung, Inhwa; Park, Min
Abstract: Polyamide 66/nanocarbon (PA66/NC) composites were fabricated by dispersing various carbon nanomaterials, namely graphene nanoplatelets, graphene oxide, and multi-walled carbon nanotubes, into polymer matrixes via melt mixing. Various amounts and types of fillers were used with the goal of optimizing the mechanical properties of the resulting composites. Especially, Young's modulus, yield stress, tensile strength, and elongation of the various PA66/NC composites were compared. To allow precise judgments regarding increases or decreases in each of these quantities, hypothesis testing of the equality of means was performed using a one-tailed test. As mechanical properties are closely related with the dispersion of the filler within the matrix, we quantified the dispersibility by analyzing frequency distributions of light intensity transmitted through film samples. We found that a 1:1 hybrid filler of graphene oxide and multi-walled carbon nanotubes was effective for enhancing mechanical properties. The hybrid filler of graphene nanoplatelets and multi-walled carbon nanotubes was also effective for enhancing mechanical properties. By applying 1 wt% of the hybrid filler of graphene oxide and multi-walled carbon nanotubes into polyamide 66, the Young's modulus increased 26.3%, yield stress increased 33.7%, and tensile strength increased 1.3% compared with that of unmixed polyamide 66.